Cost of Justice and Exclusion - Sohaib, Ahmad; Shafique, Muhammad; Ali, Hafiz Fawad; Iftikhar, Yasir; Nadeem, Kashif (European Scientific Journal, ESJ, 2019)
The main objective of an economic system is to help people in satisfying the basic necessities of life without compromising an individual’s freedom. However, almost every society in the world depicts a clear division among people. Some individuals have access to all facilities required for a decent life, while others are excluded from having such facilities. This paper focuses on testing whether this is the case with the judicial system of Pakistan. Based on the philosophical approach towards life, this paper assumes that the foundation on which the current judicial system has been evolved is exclusive in its nature. The paper attempts to show that the exclusive nature of the judiciary cannot become inclusive until we bring the philosophy of the current economic system in line with reality. The paper claims that the philosophy of the current economic system protects the interest of rich and wealthy people. Hence, all sub-systems such as political, judicial, and executive mainly facilitate and promote the welfare of rich people. The final outcome is in favor of those who are wealthy and have high intercept in the society in terms of money and social capital (links with influential people such as politicians/bureaucrats/army generals, etc.). On the other hand, the intuitional framework of the judiciary is less likely to help those who fall into the group of people who do not have money and social capital. The paper test the presumptions empirically based on the primary data collected from Lawyers in the district courts of Islamabad. Here we compare the cost of various types of cases across courts with the average income of an average family. The average cost of almost all types of cases is higher than the average income of an average family. This shows the excludability of the judicial structure of Pakistan. The average family income is calculated from Household Integrated Economics Survey (HIES). The study suggests that a judicial structure with the agents having primary objective of settling the disputes of people are required. The current structure has flaw as it link earnings with the disputes of people. We need a society where the ills of one such as diseases, disputes, weakness, etc., should not become the source of earning for others. The study also claims that until we develop such a society, the true spirit of justice will remain a mere dream for the excluded people.